Knowledge assessment of the diversity of fish, crustaceans and molluscs in the marine waters of Maranhão State, northeast coast of Brazil - De Lima Cardoso, Rayssa [UNESP]; Do Nascimento Cavalcante, Adriana; Torres, Hetty Salvino; Nunes, Karla Bittencourt; Ferreira, Cássia Fernanda Chagas; Carvalho-Neta, Raimunda Nonata Fortes (FapUNIFESP (SciELO), 2018)
This study aimed to synthetize the knowledge on the number of species, the number of experts and identification guides of three marine taxa of the coast of Maranhão State: fish, mollusks, and crustaceans. For this research, metrics were used to classify the state of knowledge: species richness, number of exotic species, number of identification guides and specialists. The main databases of scientific journals were searched between 1990 and 2015. The state of knowledge of each marine taxonomic group ranged from one to five, five = very well-known and one = unknown. The fish taxon is represented by 303 species and the group crustaceans by 205 species, both having a knowledge state equal to three. The group of mollusks counted 81 species, being classified as two in the state of knowledge scale. The number of marine species recorded highlights the importance of public policies and national incentives aimed at increasing studies in the area of diversity, both for the development of biological conservation and maintenance measures and for the understanding of the natural resources of the region.
Avaliação do conhecimento sobre a diversidade de peixes, crustáceos e moluscos nas águas marinhas do estado do maranhão, costa nordeste do Brasil
Keywords: Biodiversity; Maranhão; Species; State of knowledge